Anterior cruciate ligament reconstruction in patients over age sixty years. Issue 6 (November 2017) - Troyer, Joshua D.; Flanigan, David C.; Kaeding, Christopher C.; Magnussen, Robert A.
Abstract : Background: We sought to determine outcomes of anterior cruciate ligament reconstruction (ACLR) in patients over 60 yr of age at the time of reconstruction. Methods: All patients over the age of 60 yr who underwent ACLR at our institution between 2005 and 2014 were identified. Patients were subsequently contacted and each completed a questionnaire that included a Knee injury and Osteoarthritis Outcome Score (KOOS), Marx and Tegner Activity Scores, patient satisfaction with the operation, and details of any subsequent surgical procedures on the index knee. Results: Ten patients met inclusion criteria, and all 10 were contacted at a mean of 4.4 yr after ACLR (range: 1.3-9.4 yr). The mean KOOS scores for each subscale were: pain 95.9, symptoms 90.4, activities of daily life 95.0, sport and recreation function 80.5, and knee-related quality of life 79.7. No patient underwent repeat surgery on the index knee. The median Tegner activity score was 3 (range, 2-6). Nine of the 10 patients reported that they were able to return to their preoperative activity level. All patients were subjectively satisfied with the results of their surgery and stated that they would do the operation again if given the choice. Conclusions: ACL reconstruction in patients over the age of 60 yr yields excellent patient-reported outcomes, high rates of return to preinjury activity level, and low revision risk when performed for symptomatic instability in the absence of significant osteoarthritis.